Anomalies in milk line: Case report of two cases - Mani Krishna; Taiba Khan; Asim Khan (Wolters Kluwer Medknow Publications, 2020)
Congenital anomalies of breast, especially polymastia and polythelia, confuse clinicians because of their varied presentations, associated renal anomalies, and pathologies arising in them. Case 1: A 30-year-old Asian Indian female presented with swelling in left inguinal region since 2 years, increased in size in last 2 months with history of milk discharge. Diagnosis of ectopic breast tissue inguinal region with lactational changes was made on fine-needle aspiration cytology (FNAC). Case 2: A 28-year-old female presented with complaints of bilateral axillary mass for 2 years which is gradually increasing in size and associated with pain and discomfort along with intrareolar polythalia (left breast). FNAC was done from both axillary swelling which came out to be the fibroadenoma in ectopic breast tissue. Both the cases are discussed because of their rarity and to screen ectopic breast tissue for any pathology during routine screening of breast.